PhD Study and Research in Chartered Management - Iqbal Shaukat (Indonesian Journal Publisher, 2025)
Chartered management qualification is essential in this age of management globalization. As chartered managers, we study the different streams of management. As chartered managers, we study the buying and selling material and the economic order quantity of material management. As the chartered manager, we study all the aspects of material management related to production and operation management. As chartered managers, we study operation management in detail and study cases. In the chartered manager we can learn about the utilization of resources under the principles of operation management, in operation management we study the best location of resources and their utilization according to the needs. In chartered management, we study quality control and project management.